A Computational Thinking Assessment Tool on Text- Based Programming - Wang, Jihan; Zhang, Wei; Zeng, Xinyao; Li, Panpan (2023 IEEE 12th International Conference on Educational and Information Technology (ICEIT), 2023)
The assessment of computational thinking (CT) skills based on text-based programming is a necessary part of the implementation of CT education in higher education. However, the current research on CT assessment is mostly single-approach, which is not effective in accurately measuring numerous competencies of CT skills and has the disadvantage of assessment limitation. In order to solve the problem of assessment limitations, this paper defines the content of CT evaluation from the perspective of text-based programming and constructs a multidimensional test method. Different test schemes are selected according to the characteristics of CT skills, and assessment tools are developed by combining the question test, programming test and scale survey, and the assessment tools are used to evaluate and analyze learners' CT skills from qualitative and quantitative perspectives. The results show that the evaluation indicators and test questions designed on text-based programming are more consistent with the evaluation objectives. And the approach of evaluating CT skills from both qualitative and quantitative perspectives can reflect learners' CT skills more comprehensively and accurately.